Investigating the Differences Between Prepared and Spontaneous Speech Characteristics: Descriptive Approach - Gatiyatullina, Galiya M.; Gorodetskaya, Ludmila A.; Solnyshkina, Marina I.; Gafiyatova, Elzara V. (International Journal of Criminology and Sociology, 2022)
In the modern EFL paradigm, pre-task planning time is viewed as a norm. Pre-task planning time is one of the central concerns of teachers, test-developers, as well as researchers. Pre-task planning is planning a speech before performing a task, and it also involves rehearsal and strategic planning. The paper addresses the problem of pre-task planning advisability for A2 Russian EFL speakers. The research presented in this paper examines the structure, breakdown, repair, syntactic complexity, lexical diversity as well as the accuracy of the discourse produced by 145 Russian participants of the English language competition held in Kazan, Russia, in January 2020. The discourse analysis revealed that the pre-task time is used by A2 EFL speakers not only to focus on a dialog but also to elicit a topic text from memory, thus focusing on form rather than meaning. Hence, in A2 tests prioritizing meaning over form and measuring the ability for spontaneous speech, the one-minute pre-task planning time is viewed as questionable.